Guds ord og døden: Danske teologer og blodskam 1680-1770 - Jonsson, Mår (Kirkehistoriske Samlinger, 2003)
In 16th and 17th century Northern Europe incest was defined by the Word of God as expressed in Leviticus 18 and 20. Secular and religious authorities agreed that execution was the appropriate punishment for incestuous behaviour. In Denmark, only rarely the king used his right to change such verdicts to lifelong prison or exile. In the Danish and Norwegian codes of law published in 1683-1687, however, this royal prerogative was stated in such a manner that the king now had the duty to consider all cases where people had been sentenced to death. Since incest was defined according to Leviticus he soon started to ask for the opinion of theologians at the University of Copenhagen on single cases. This went on for almost 50 years and the theologians wrote copious declarations, gradually changing from a strict interpretation of Leviticus to a milder view that recommended lesser penalties. Most of the time the king accepted their conclusion, but less and less as time passed, and around 1730 he stopped asking them for advice. Biblical influence on law making was dwindling and continued to do so. Before the end of the 18th century, even the definition of incest had become based on ideas derived from natural law instead of the Word of God.